The Influence of Host Attractiveness, Interactivity, and Perceived Enjoyment on Impulse Buying Behavior among Live Streaming Commerce Users in Kendari, Indonesia - Muhamad Ridhayanto (Manajemen Multitalenta Indonesia, 2026)
The rapid development of live-streaming commerce has transformed online shopping by integrating real-time product demonstrations, entertainment, social interaction, and purchasing activities within digital platforms. This study aims to examine the influence of host attractiveness, interactivity, and perceived enjoyment on impulse buying behavior among live-streaming commerce users in Kendari, Indonesia. A quantitative research approach was employed using primary data collected through questionnaires distributed to 100 respondents who had purchased products through TikTok Shop or Shopee Live. Respondents were selected using purposive sampling based on specific criteria, including being at least 17 years old and having purchased products through live-streaming commerce within the previous six months. The data were analyzed using IBM SPSS Statistics through descriptive analysis, validity and reliability testing, classical assumption tests, and multiple linear regression analysis. The findings indicate that host attractiveness does not have a significant effect on impulse buying behavior, as demonstrated by a t-value of 1.543 and a significance value of 0.126. Similarly, interactivity does not significantly influence impulse buying behavior, with a t-value of 1.419 and a significance value of 0.159. In contrast, perceived enjoyment has a positive and significant effect on impulse buying behavior, with a t-value of 4.814 and a significance value of 0.001. These findings indicate that consumers’ pleasurable, entertaining, and emotionally engaging experiences are more influential in stimulating spontaneous purchases than host attractiveness or direct interaction. The study contributes to the literature on live-streaming commerce and provides practical implications for online sellers and marketers to prioritize enjoyable and engaging content strategies to encourage impulse buying.